2019
DOI: 10.1038/s12276-019-0275-6
|View full text |Cite
|
Sign up to set email alerts
|

The flagellin-TLR5-Nox4 axis promotes the migration of smooth muscle cells in atherosclerosis

Abstract: We hypothesized that NADPH oxidase 4 (Nox4) is involved in the formation of neointimal atherosclerotic plaques through the migration of smooth muscle cells (SMCs) in response to flagellin. Here, we demonstrate that TLR5-mediated Nox4 activation regulates the migration of SMCs, leading to neointimal plaque formation in atherosclerosis. To investigate the molecular mechanism by which the TLR5-Nox4 cascade mediates SMC migration, we analyzed the signaling cascade in primary vascular SMCs (VSMCs) from wild-type (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Most NOX proteins generate O 2 − , but NOX4 catalyzes the reduction of molecular oxygen to H 2 O 2 . This feature gives NOX4 some specific roles in different cellular functions, such as proliferation (Petry et al, 2006), differentiation (Clempus et al, 2007), migration (J. Kim et al, 2019; Lyle et al, 2009; Meng et al, 2015; M. Zhang, Xu, Qiu, & Jiang, 2019), apoptosis (Pedruzzi et al, 2004), senescence (Canugovi et al, 2019), matrix secretion (Hecker et al, 2009), and angiogenesis (A. Z. Chen, Li, Zhou, & Min, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Most NOX proteins generate O 2 − , but NOX4 catalyzes the reduction of molecular oxygen to H 2 O 2 . This feature gives NOX4 some specific roles in different cellular functions, such as proliferation (Petry et al, 2006), differentiation (Clempus et al, 2007), migration (J. Kim et al, 2019; Lyle et al, 2009; Meng et al, 2015; M. Zhang, Xu, Qiu, & Jiang, 2019), apoptosis (Pedruzzi et al, 2004), senescence (Canugovi et al, 2019), matrix secretion (Hecker et al, 2009), and angiogenesis (A. Z. Chen, Li, Zhou, & Min, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The exact signaling events that lead to transcriptional activation of IGF and TGF-β1 should be further examined. It is established that Nox4 activates NF-κB and that NF-κB activates TGF-β genes [ 32 35 ]. It has also been reported that Nox signaling leads to activation of Smad pathway [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that activated P38MAPK has been found in human AD brain tissue, furthermore, recent studies have corroborated the fact that there is an interaction between phospho-PKA and phospho-P38MAPK expression. In most systems, MAPK stimulates the transcriptional activity of NF-kB, while PKA suppresses it [33]. In addition, PKA activator-SKF38393 was in fact developed as potential therapeutics for AD with purpose to block P38MAPK phosphorylation [34].…”
Section: Discussionmentioning
confidence: 99%